Ethics, aesthetics, and the beyond of language - Hughes, Robert, 1968- (SUNY series, insinuations., 2010)
This book explores the relationship between literature and ethics, showing how literature and art work to open up a part of ethics that resists traditional philosophy. Focusing on three American Romantic texts--Wieland, "The Legend of Sleepy Hollow," and the Marble Faun--Robert Hughes demonstrates how each dramatizes the ethical, psychological, and existential imperative to put the experience of our own traumatic limits (death, morality, and being) into poetic language. To develop the theoretical stakes of these literary readings, Hughes also draws on four twentieth century continental thinkers--Jacques Lacan, Martin Heidegger, Emmanuel Levinas, and Alain Badiou--each of whom, in his own way, proposed aesthetics or art as an approach to this dimension of ethics. The book also points to an overlooked common lineage, descending from German Romanticism, between American Romanticism and contemporary post-Romantic continental thought: a shared supposition about the limits of reason.